(untitled) (Journal of Computational Mathematics, 2003)
This is the third part of the paper for the rotated Q_1 nonconforming element on quadrilateral meshes for general second order elliptic problems. Some optimal numerical formulas are presented and analyzed. The novelty is that it includes a formula with only two sampling points which excludes even a Q_1 unisolvent set. It is the optimal numerical integration formula over a quadrilateral mesh with least sampling points up to now.